Hypertrophic spinal pachymeningitis associated with human T-cell lymphotrophic virus-1 infection and Sjogren's syndrome: A case report and brief literature review. (2018) - Bureta, Costansia A.; Abematsu, Masahiko; Tominaga, Hiroyuki; Saitoh, Yoshinobu; Kawamura, Ichiro; Nagano, Satoshi; Setoguchi, Takao; Ishidou, Yasuhiro; Yamamoto, Takuya; Komiya, Setsuro
Highlights: Hypertrophic pachymeningitis is a rare disease characterized by inflammatory fibrosis and thickening of the dura mater. There is an established relationship between HTLV-1 infection and primary SS. MRI is considered to be the best radiological diagnostic tool. Laminectomy and excision of the thickened dura has shown to be the best mode of treatment. Due to the risk of recurrence, long-term follow-up is very important for correct evaluation of surgical treatment of HSP. Abstract: Introduction: Reports of hypertrophic spinal pachymeningitis associated with human T-cell lymphotrophic virus-1 (HTLV-1) infection and Sjogren's syndrome in the English literature are still very rare. Presentation of case: We hereby present a case of a 78-year-old female with a history of lower extremity weakness after a fall, which fully resolved after conservative treatment. However, the symptoms recurred 4 years later, and the patient became unable to walk. The patient had no superficial or deep sensation below the level of T9, and she also had urinary retention. Magnetic resonance imaging showed that hypertrophic dura mater was compressing the spinal cord from T2 to T10. Blood testing revealed increased anti-HTLV-1 antibody, rheumatoid factor, elevation of anti-SS-A antibody and antinuclear antibody. The cerebrospinal fluid contained markedly elevated levels of total protein and cell numbers. Biopsy of the labial gland of the lip revealed chronic sialadenitis. Discussion: In collaboration with a neurologist, we diagnosed this patient with hypertrophic spinal pachymeningitis associated with HTLV-1 infection and Sjogren's syndrome. We performed laminectomy at the affected spinal levels, resected the thickened dura, and maintained the patient on steroid therapy. The patient attained a marked recovery; she could walk with a cane and her urinary retention was improved. Conclusion: For the management of HSP associated with HTLV-1 and SS, we recommend surgical decompression with subsequent prolonged steroid therapy and prolonged close monitoring to achieve a good long-term outcome.